Huddling Conserves Energy, Decreases Core Body Temperature, but Increases Activity in Brandt's Voles (Lasiopodomys brandtii) - Sukhchuluun, Gansukh; Zhang, Xue-Ying; Chi, Qing-Sheng; Wang, De-Hua (Frontiers in Physiology, 2018)
Huddling as social thermoregulatory behavior is commonly used by small mammals to reduce heat loss and energy expenditure in the cold. Our study aimed to determine the effect of huddling behavior on energy conservation, thermogenesis, core body temperature (Tb) regulation and body composition in Brandt’s voles (Lasiopodomys brandtii). Adult captive-bred female Brandt’s voles (n=124) ( 50 g) in 31 cages with 4 individuals each were exposed to cool (23±1°C) and cold (4±1°C) ambient temperatures (Ta) and were allowed to huddle or were physically separated. The cold huddling (Cold-H) groups significantly reduced food intake by 29 % and saved digestible energy 156.99 kJ/day compared with cold separated groups (Cold-S); in cool huddling groups (Cool-H) the reduction in food intake was 26 % and digestible energy was saved by 105.19 kJ/day in comparison to the separated groups (Cool-S). Resting metabolic rate (RMR) of huddling groups was 35.7% and 37.2% lower than in separated groups at cold and cool Tas, respectively. Maximum non-shivering thermogenesis (NSTmax) of huddling voles was not affected by Ta, but in Cold-S voles it was significantly increased in comparison to Cool-S. Huddling groups decreased wet thermal conductance by 39% compared with separated groups in the cold, but not in the cool Ta. Unexpectedly, huddling voles significantly decreased Tb by 0.25-0.50°C at each Ta. Nevertheless, activity of Cold-H voles was higher than in Cold-S voles. Thus, huddling is energetically highly effective because of reduced metabolic rate, thermogenic capacity and relaxed Tb regulation despite the increase of activity. Therefore, Brandt’s voles can remain active and maintain their body condition without increased energetic costs during cold exposure. This study highlights the ecological significance of huddling behavior for maintenance of individual fitness at low costs, and thus survival of population during severe winter in small mammals.